المحاسبة في القطاع العام - حقيقي سميرة, كرفي حليمة (My University, 2022)
The object of this work ،which is tagged with public accounting ،is to define accounting and its role in the public sector, then to rely on the descriptive analytical approach, thestudy period extended from December to Mayat achaacha mostaganem hospital. Through this study, the following results were obtained: - The general budget is a main tool used to analyze the desired goals,and it is effective and qualified for implementation it also qualifies us that the manager is the only one decides to spend
دراسة حالة المؤسسةالإستشفائية عشعاشة
Keywords: Revenue – general expenses-general accounting- budget